THE XINJIANG UYGHUR AUTONOMOUS REGION'S HISTORICAL BACKGROUND AND UYGHUR HUMAN RIGHTS SITUATION (Isagoge - Journal of Humanities and Social Sciences, 2021)
The Xinjiang Uyghur Autonomous Region (XUAR) started in 1865 when Tsarist Russia managed gradually to conquer the western part of Turkestan. Subsequently, The region Western Turkestan was established. Western Turkestan was divided into five republics with the establishment of the Soviet Union in 1924: Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan, and Tajikistan. In 1949, when the Chinese Communist Party (CCP) won the election against Kuomintang (KMT), The region's name was changed to Uyghur Autonomous Region of Xinjiang. The race of Xinjiang (New Borders) can be separated into two groups: non-Turkic people (Han Chinese, Russians, Indians, and Manchurians) and Turkic people (Xinjiang indigenous). Uyghur, Kazakh, Uzbek Kirghiz, and Tajik are all Turkic languages, with the Uyghurs having the biggest community. Based on this description, this study examines the history of the Uyghur Autonomous Region of Xinjiang and its existence within the framework of international relations as well as the human rights conditions of Uyghurs.